Auditoría de cumplimiento en la cooperativa interprovincial Macuchi, cantón La Maná provincia de Cotopaxi año 2021. - Carrión Figueroa, Kelly Brishite (2023)
The current research project resulted in the execution of a compliance audit in order to know the state in which the cooperative is in the operational, administrative, accounting, and tax area. The purpose is to contribute with improvement measures to the provided services by the cooperative. It was established in the theoretical framework the essential concepts for the development of the project such as the Compliance Audit. It included the verification or examination of the operational, administrative, accounting and tax, economic and other operations of the entity to establish the operations that have been carried out in accordance with the legal, regulatory, statutory, and procedural standards, as well as the objectives, classification, and phases of the entity. In the methodological framework, it was addressed by hypotheses of descriptive and applied research by using the methods, techniques, and instruments such as interview, surveys, and SWOT matrix for the development of this topic. In the proposed framework, the audit phases were developed, for its execution an audit program was carried out where each phase is detailed with its respective activities. It began with the preliminary phase, firstly a general diagnosis of the entity was made. The components to be audited were determined, so being evaluated in the Internal Control System within the execution phase in which the achievement of the functions of the credit committee also was evaluated. It showed a double moderate level, the first one about confidence with a result of 70% and the other about the level of risk at 30%.